2020
DOI: 10.1080/15384047.2020.1798696
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of selective target engagement by small-molecule sphingosine kinase inhibitors using the Cellular Thermal Shift Assay (CETSA)

Abstract: The recently renewed interest in scientific rigor and reproducibility is of critical importance for both scientists developing new targeted small-molecule inhibitors and those employing these molecule in cellular studies, alike. While off-target effects are commonly considered as limitations for any given smallmolecule inhibitor, the ability of a given compound to distinguish between enzyme isoforms is often neglected when employing compounds in cellular studies. To call attention to this issue, we have compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…PF-543 and ABC) that enhanced cell death in response to MTX, we next determined whether the combination of MTX+SKIs enhanced the cell surface exposure of CRT. Both PF-543 and ABC were employed at concentrations that would inhibit both SphK1 and SphK2, as we have previously determined by direct target engagement assays in whole cells (Hengst et al, 2020). As shown in Figure 3A, PF-543 alone had no effect on the cell surface exposure of CRT in DLD-1 cells, compared to vehicle treated cells, as determined by flow-cytometry employing the above described assay.…”
Section: Sphingosine Kinase Inhibition Enhances Mtx-induced Cell Surface Expression Of Crt and Atp Releasementioning
confidence: 85%
See 1 more Smart Citation
“…PF-543 and ABC) that enhanced cell death in response to MTX, we next determined whether the combination of MTX+SKIs enhanced the cell surface exposure of CRT. Both PF-543 and ABC were employed at concentrations that would inhibit both SphK1 and SphK2, as we have previously determined by direct target engagement assays in whole cells (Hengst et al, 2020). As shown in Figure 3A, PF-543 alone had no effect on the cell surface exposure of CRT in DLD-1 cells, compared to vehicle treated cells, as determined by flow-cytometry employing the above described assay.…”
Section: Sphingosine Kinase Inhibition Enhances Mtx-induced Cell Surface Expression Of Crt and Atp Releasementioning
confidence: 85%
“…cell surface expressed CRT, and secretion of ATP and high mobility group box 1; HMGB1) in enucleated cancer cells indicating that the DNA damaging activity of MTX is not required for ICD induction (Obeid et al, 2007b). To examine the effects of altered sphingolipid metabolism, we first treated the mouse CRC cell line CT-26 (routinely used for ICD experiments (Kepp et al, 2014)) with multiple SphK inhibitors including, PF-543 (Schnute et al, 2012), ABC294640 (ABC) (French et al, 2010) and SK1 We recently examined the isoform selectivity of multiple SKIs using the Cellular Thermal Shift Assay (CETSA), a whole cell assay of target engagement (Hengst et al, 2020). These studies revealed that at the concentrations commonly employed in the literature the SKIs tested, including PF-543 (SphK1-selective), ABC (SphK2-selective) and SK1-I (SphK1-selective), target engaged both SphK1 and SphK2.…”
Section: Inhibition Of the Sphingosine Kinases (Sphks) Enhances Mtx Induced Cell Deathmentioning
confidence: 99%
“…For CETSA, experiments were performed according to the previously published protocols with minor modifications [ 25 ]. The primary neurons in 100 mm dishes were collected with PBS containing protease inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…Target engagement assay of celastrol with HMGB1 was performed the same with previous article with minor modify [25]. The primary neurons in 100 mm dishes were collected with PBS containing protease inhibitor.…”
Section: Pull Down Tmt Labeling and Targets Validationmentioning
confidence: 99%